2015
DOI: 10.3390/cancers7020815
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age on the Detection and Management of Breast Cancer

Abstract: Currently, breast cancer affects approximately 12% of women worldwide. While the incidence of breast cancer rises with age, a younger age at diagnosis is linked to increased mortality. We discuss age related factors affecting breast cancer diagnosis, management and treatment, exploring key concepts and identifying critical areas requiring further research. We examine age as a factor in breast cancer diagnosis and treatment relating it to factors such as genetic status, breast cancer subtype, hormone factors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
203
0
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(221 citation statements)
references
References 162 publications
(172 reference statements)
10
203
0
8
Order By: Relevance
“…Breast cancer is the most common invasive cancer in women, affecting approximately 12% of females worldwide [1]. In cancer studies, tumour cell lines are widely used as simple models that provide essential tools for more complex biological analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is the most common invasive cancer in women, affecting approximately 12% of females worldwide [1]. In cancer studies, tumour cell lines are widely used as simple models that provide essential tools for more complex biological analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, these results may reflect more, the involvement of BRCA1 gene mutations in development of breast cancer in Egypt. Since the risk of breast cancer increases steadily with age (McGuire et al, 2015), in the present study the relative risk estimation revealed that the females with BRCA1 mutation and with age more than 40 years has 1.3 folds increased risk for the development of breast cancer compared to females with age less than 40 years. Beclin 1 is an essential modifier of the autophagic process and has been implicated in the tumorigenesis of many types of cancers.…”
Section: Discussionmentioning
confidence: 46%
“…It has been estimated that in 2015, around 268,600 new cancer cases and 72,000 cancer-related deaths occurred in China and 2.8 million women were affected by breast cancer (McGuire et al, 2015). According to the subtyping guidelines by St. Gallen International Breast Cancer Congress (Goldhirsch et al, 2011), basal-like type (triple-negative breast cancer type mainly) is more invasive due to the lack of estrogen receptor, progesterone receptor, and human epidermal growth factor receptor 2 expressions and overexpression of basal-like molecular markers in breast cancer cells, making them insensitive to either molecular targeting or endocrine treatment (Goldhirsch et al, 2011).…”
Section: Introductionmentioning
confidence: 99%